1994
DOI: 10.1111/j.1439-0426.1994.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Spirulina feeding on muscle protein deposition in red sea bream, Pagrus major

Abstract: As the fact that feeding Spirulina can improve carcass uality of fish, this study describes the effect on muscle protein in red sea bream, Pagrus major. The ;fsh were fed on a diet supplemented with 2% Spirulina for 95 days under commercial rearing conditions. Spirulina feeding elevated protein synthesis, which was estimated by muscle RNA/DNA and RNA/protein ratios. Muscle protein was fractionated into sarco lasmic, myofibrillar, alkali-soluble and stromal fractions. The stromal fraction was si nificantly gigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
(5 reference statements)
2
31
0
1
Order By: Relevance
“…By contrast, the results of other studies revealed positive effects of spirulina on the growth of other fish species, including the nibbler Girella punctata Gray (Nakazoe et al, 1986), striped jack Pseudocaranx dentex (Watanabe et al, 1990), red sea bream Pagrus major (Mustafa et al, 1994), rohu Labeo rohita (Nandeesha et al, 2001), Nile tilapia (Lu et al, 2004), Siberian sturgeon Acipenser baeri (Palmegiano et al, 2005) of experimental diets supplemented with spirulina, and the results showed positive effects.…”
Section: Discussionmentioning
confidence: 88%
“…By contrast, the results of other studies revealed positive effects of spirulina on the growth of other fish species, including the nibbler Girella punctata Gray (Nakazoe et al, 1986), striped jack Pseudocaranx dentex (Watanabe et al, 1990), red sea bream Pagrus major (Mustafa et al, 1994), rohu Labeo rohita (Nandeesha et al, 2001), Nile tilapia (Lu et al, 2004), Siberian sturgeon Acipenser baeri (Palmegiano et al, 2005) of experimental diets supplemented with spirulina, and the results showed positive effects.…”
Section: Discussionmentioning
confidence: 88%
“…Feeding red sea bream (Pagrus major) for 95 days on a diet supplemented with 2% Spirulina sp. elevated the protein synthesis of the fish, and the stromal fraction of the muscle protein was significantly higher in the Spirulina-fed group (Mustafa et al, 1994). A study on Nile tilapia revealed that feeding 25% of Chlorella spp.…”
Section: Growth and Feed Conversion Efficiency Upon Feeding Desmodesmmentioning
confidence: 99%
“…compare to diet without Spirulina sp. (Mustafa et al 1994). Diets containing algae protein from Hydrodictyon reticulatum (Appler 1985) and Cladophora glomerata (Appler & Jauncey 1983) also displayed the same effect, where low lipid content was observed in the Nile tilapia muscle.…”
Section: Discussionmentioning
confidence: 85%